Using Speed Reading and Extensive Reading Activities to Improve Students’ Reading Fluency - Sri Wardani (Jurnal Pendidikan Humaniora, 2015)
Abstract: This study examines the implementation of Speed Reading and Extensive Reading activities to improve students’ reading fluency of students. Using a Classroom Action Research, Speed Reading and Extensive Reading activities was applied in 2 cycles with 2 x 45 minutes per week. Speed Reading and Extensive Reading activities were taught using three phase techniques: Pre-Reading, Whilst-Reading, and Post-Reading. Speed Reading was implemented through some techniques including scanning, skimming, and repeated reading. Meanwhile, Extensive Reading was applied by asking students to read a text at home. Assessment was conducted by giving a reading fluency test after each cycle to check the students’ progress. The other data: observation checklist, field notes, and questionnaire were utilized to complete the study. The result of the study indicated that Speed Reading and Extensive Reading activities benefited students by making them aware of using certain strategy to understand the meaning of text quickly. In the end of cycle 2, it was found that most of the students were successful to become fluent readers. In addition, students’ confidence increased and Speed Reading and Extensive Reading encouraged a positive attitude towards reading fluency. Key Words: speed reading, extensive reading, reading fluency